1990
DOI: 10.1029/gl017i012p02193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of time‐ and frequency‐domain techniques for wind velocity estimation using multiple‐receiver MF radar data

Abstract: Multiple‐receiver MF radar returns from the mesosphere are used to investigate the relationship between spaced antenna (SA), radar interferometry (RI), and imaging Doppler interferometry (IDI) wind estimation techniques. Our results show that frequency‐domain (RI and IDI) and time‐domain (SA) techniques yield almost identical results under high SNR conditions suitable for SA full correlation analysis (FCA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Franke et al, 1990;Meek and Manson, 1987;Brown et al, 1995;Turek et al, 1995Turek et al, , 1998, while the ESP alignment showed similar agreement to that of Vandepeer and Reid (1995a) between 70 and 84 km. Despite this agreement Holdsworth and Reid (1995b) were careful not to suggest that the volume scatter was applicable experimentally, or that the interferometric techniques would fail experimentally.…”
Section: Imaging Doppler Interferometry and The Volume Scatter Situationmentioning
confidence: 52%
See 4 more Smart Citations
“…Franke et al, 1990;Meek and Manson, 1987;Brown et al, 1995;Turek et al, 1995Turek et al, , 1998, while the ESP alignment showed similar agreement to that of Vandepeer and Reid (1995a) between 70 and 84 km. Despite this agreement Holdsworth and Reid (1995b) were careful not to suggest that the volume scatter was applicable experimentally, or that the interferometric techniques would fail experimentally.…”
Section: Imaging Doppler Interferometry and The Volume Scatter Situationmentioning
confidence: 52%
“…Furthermore, they advocate the use of an extra receiving antenna in order to calculate the normalized phase discrepancy as a further criterion. In contrast, Franke et al (1990) successfully applied interferometric analyses without use of any single scatterer criterion. The "single scatterer" and "volume scatter" situation assumed by the FCA represent limiting cases of the type of scattering mechanisms expected for MF radars.…”
Section: Imaging Doppler Interferometry and The Volume Scatter Situationmentioning
confidence: 99%
See 3 more Smart Citations